Synthesis, Structural and Antibacterial Study of Some Metal Ion Dithiocarbamate-Azo Complexes - Al-Hasani, Thanaa J; Al-Taie, Mustafa K (Al-Nahrain Journal of Science, 2015)
Sodium diethyldithiocarbamate (DTC) forms stable colored [MII(DTC)2] complexes where MII = Mn, Fe, Co, Ni, Cu and Zn. The characterization data suggested square planar geometrical structure for CoII, NiII and CuII complexes and a tetrahedral structure for MnII, FeII and ZnII complexes. Six new complexes of general formula [M(DTC)2PAN] where PAN=1-(2-Pyridyl azo)-2-naphthol, were synthesized by using two different routes of preparation. The structures of the complexes are discussed in relation to the analytical, spectroscopic, magnetic and conductivity data. The DTC-ligand exhibits bidentate behavior acting as S,S`-donors in all complexes. PAN was also behave as bidentate N,N` ligand. The electronic spectra along with magnetic moment values suggested an octahedral structure for [M(DTC)2PAN] complexes. The biological activity for ligands and the prepared complexes were studied against Escherichia Coli, Pseudomonas (G-) and Staphylococcus Aureus, Bacillus (G+) bacteria. Some of the complexes have a relatively strong deactivating capacity against the specimen of bacteria. The presence of PAN ligand increased the inhibition zone.